Analisis Penggunaan Media Pembelajaran Dalam Bentuk Aplikasi Pada Guru SD Kecamatan Palembayan Kabupaten Agam - Lizawati; Abna Hidayati; Zelhendri Zen; Fetri Yeni (Jurnal Penelitian Pendidikan IPA, 2025)
The transformation of education in the Society 5.0 era has accelerated the integration of digital technology into teaching and learning. This study examines the use of application-based learning media by elementary school teachers in Palembayan Subdistrict, Agam Regency, and explores the factors influencing teachers’ digital competence and the challenges encountered in implementation. Using a mixed-methods approach, data were collected from 99 teachers through questionnaires addressing five core aspects, supported by interviews and field observations. Results show that application usage falls within a moderately favorable range, with most teachers using applications two to three times per week. Frequently used platforms include Canva and Wordwall, valued for their ease of use and support for interactive visual learning. Teachers’ digital skills are influenced by variables such as teaching experience, educational background, device access, and internet stability. Key challenges include limited technological infrastructure, unstable connectivity, and difficulties adapting application features to curriculum content. Despite these barriers, many teachers demonstrate adaptability through independent learning and collaboration. The study highlights the need to strengthen digital competence through ongoing training, promote the development of user-friendly educational applications, and improve infrastructure to ensure inclusive and effective digital transformation in elementary education.